Atributos de la gastronomía tradicional del pueblo de Moche, para el desarrollo del turismo gastronómico. - Reyes Aranda, Patricia Mariela (2016)
This research paper entitled attributes of traditional cuisine of the people of Moche, for the development of gastronomic tourism, is aimed at identifying the attributes of the traditional cuisine of the Moche people to consider it within the tourism industry._x000D_ The tradition is evidenced in the heritage to leave the contribution of the ancient Moche culture, which has been transmitted from generation to generation mainly from parents to children; also the characteristic aroma, the flavor, the Seasoning and presentation of the food. The variety of dishes is evident in the traditional way of preparing dishes, as well as acceptance of tourists in terms of variety, seasoning and presentation thereof, and the possibility of developing culinary tourism._x000D_ Finally the people of Moche has traditional inputs, which are evidenced by the particularity of flavor that provide healthy meals, the influence of natural factors that allow the planting and cultivation of these inputs._x000D_ We use the Ethnographic, deductive-inductive method, in addition to techniques such as direct participant observation, interview 15 cooks and 15 farmers more representative of the people of Moche farmers, and the survey of 160 tourists who arrived at the same weekends during the September and October 2015.